The Care Leavers' annual lecture: University of Dundee, 30 October 2015 - Laura Beveridge (Scottish Journal of Residential Child Care)
I'm going to share my care journey with you. For me to do this I'll take you back to a wee town called Tranent in East Lothian, Scotland, where I lived with my mum, step-dad and younger brother and sister. I spent 10 years there, mostly hiding under my bed. I was terrified of my step-dad. The only escape I had was my Disney films: like Sleeping Beauty, The Little Mermaid and Cinderella. I'd watch each right to the end to watch the little clip of Disney World in Florida where I'd see a glimpse of a happy family: a mum, dad with their little girl and boy as they'd walk through the gates of Magic Kingdom in Orlando, Florida. Their eyes filled with excitement and happiness just being there together, meeting their favourite characters like Mickey, Minnie and Cinderella! Their wee faces would light up as they watched the fireworks light up the night sky and they'd watch on in amazement at the electrical parade making its way down Main Street in the Magic Kingdom as it played all the classic Disney songs. That was my dream. To be happy, to be in a family full of love and laughs. I spent so many nights looking out of my bedroom window wishing upon a star that my dream would come true one day.